Literature about Latin America during the Era of World War I - Thomas M. Leonard (Latin American Research Review, 2019)
This essay reviews the following works: The Intelligence War in Latin America, 1914–1922. By Jamie Bisher. Jefferson, NC: McFarland and Company, 2016. Pp. viii + 414. $75.00 paperback. ISBN: 9780786433506.   Beyond Geopolitics: New Histories of Latin America at the League of Nations. Edited by Alan McPherson and Yannick Wehrli. Albuquerque: University of New Mexico Press, 2015. Pp. viii + 269. $55.00 hardcover. ISBN: 9780826351654.   Treacherous Passage: Germany’s Secret Plot against the United States in Mexico during World War I. By Bill Mills. Lincoln: University of Nebraska Press, 2017. Pp xii + 256. $29.95 hardcover. ISBN: 9781612348544.   Colombia and World War I: The Experience of a Neutral Latin American Nation during the Great War and Its Aftermath, 1914–1921. By Jane M. Rausch. Lanham: Lexington Books, 2014. Pp. vii + 137. $91.00 hardcover. ISBN: 9780739187739.   Latin America and the First World War. By Stefan Rinke. Translated by Christopher W. Reid. New York: Cambridge University Press, 2017. Pp. viii + 297. $29.99 paperback. ISBN: 9781107566064.